Pengaruh Kedisiplinan Guru terhadap Hasil Belajar Siswa Kelas VI pada Mata Pelajaran PAI - Saifudin; Muhammad Afifuddin; Khusnul Khotimah (IBTIDA, 2022)
This study aims to determine teacher discipline, to determine student learning outcomes in PAI to prove the influence of teacher discipline on student achievement in PAI subjects.. This research is quantitative research and the research population is the sixth-grade students at SDI Ar-roudloh, totaling 26 people. Data collection was carried out using questionnaires and documentation of report cards for PAI subjects. Analysis of questionnaire data used percentage analysis and sted the effect using the "r" product moment test. After this research was conducted, it can be concluded that: 1) PAI teacher discipline is categorized as good, this can be seen from the percentage results obtained by 86%. 2) The learning achievement of students in the PAI SDI Ar-roudloh subjects is good, this is evidenced by the average value of the report cards showing a value of 88.7 and the correlation index "r" product moment which has been obtained is 0.0619 this shows that the correlation index "r" product moment is greater than the significance level of 5% (0.388) and at the significance level of 1% (0.496). Then the working hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This means that there is a significant influence of teacher discipline on student learning achievement.